2009
DOI: 10.1016/j.chembiol.2009.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Docking Motif-Guided Mapping of the Interactome of Protein Phosphatase-1

Abstract: The ubiquitous protein Ser/Thr phosphatase-1 (PP1) interacts with dozens of regulatory proteins that are structurally unrelated. However, most of them share a short, degenerate "RVxF"-type docking motif. Using a broad in silico screening based on a stringent definition of the RVxF motif, in combination with a multistep biochemical validation procedure, we have identified 78 novel mammalian PP1 interactors. A global analysis of the validated RVxF-based PP1 interactome not only provided insights into the conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
358
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 289 publications
(382 citation statements)
references
References 25 publications
11
358
1
7
Order By: Relevance
“…Protein serine/threonine (Ser/Thr) phosphatase-1 (PP1) is one of the most highly conserved enzymes known, and it plays a central role in a range of cellular processes, including protein synthesis, RNA splicing, cell-cycle progression, and glycogen metabolism [23,24]. A large array of regulatory subunits are associated with the PP1 catalytic subunit to determine its cellular localization and substrate specificity, mediating the control of these many physiological processes through PP1 holoenzymes [24][25][26]. There are 4 different isoforms of the PP1 catalytic subunit (a, b, c1, and c2) and each can bind to many non-substrate cellular proteins that function as regulatory subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Protein serine/threonine (Ser/Thr) phosphatase-1 (PP1) is one of the most highly conserved enzymes known, and it plays a central role in a range of cellular processes, including protein synthesis, RNA splicing, cell-cycle progression, and glycogen metabolism [23,24]. A large array of regulatory subunits are associated with the PP1 catalytic subunit to determine its cellular localization and substrate specificity, mediating the control of these many physiological processes through PP1 holoenzymes [24][25][26]. There are 4 different isoforms of the PP1 catalytic subunit (a, b, c1, and c2) and each can bind to many non-substrate cellular proteins that function as regulatory subunits.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments have previously demonstrated direct interactions between TSKS and PP1 fragments, as well as between TSKS and TSSK1 (Kueng et al 1997, Hendrickx et al 2009). While sedimentation assays indicated a reciprocal interaction between PPP1CC2 and TSSK1 in testis lysates, we sought to determine whether there was also a direct interaction between PPP1CC2 and TSSK1 in vitro.…”
Section: Interaction Between Ppp1cc2 and Tssk1 Is Mediated By Tsksmentioning
confidence: 99%
“…In a previously published study, the TSSK1 substrate TSKS was bioinformatically predicted to be a PP1-interacting protein, and subsequent in vitro experiments showed that a TSKS fragment was capable of interacting with PPP1CA (Hendrickx et al 2009), the only PP1 isoform assayed. This prediction was based on the presence of a PP1 Table 1 Testis proteins identified in a SDS-PAGE gel band after sedimentation by GST-PPP1CC1 and GST-PPP1CC2.…”
Section: Testis-specific Kinase Substrate Tsks Interacts With Ppp1cmentioning
confidence: 99%
See 1 more Smart Citation
“…PP-1c is a key regulator of protein dephosphorylation (23,24). Because PP-1c exhibits little substrate specificity, appropriate targeting of protein dephosphorylation is mediated by interaction with different regulatory subunits, which interact with PP-1c via a conserved RVXF motif as well as by secondary interactions (23-25, 32).…”
Section: Discussionmentioning
confidence: 99%